2019
DOI: 10.5588/pha.18.0098
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the yield and relative cost of active tuberculosis case-finding algorithms in Zimbabwe

Abstract: Ten districts and three cities in Zimbabwe. Objective: To compare the yield and relative cost of identifying a case of tuberculosis (TB) using the three WHO-recommended algorithms (WHO2b, symptom inquiry only; WHO2d, chest X-ray [CXR] after a positive symptom inquiry; WHO3b, CXR only) and the Zimbabwe active case finding (ZimACF) algorithm (symptom inquiry plus CXR) to everyone. Design: Cross-sectional study using data from the ZimACF project. Results: A total of 38 574 people were screened from April to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 20 publications
0
11
1
Order By: Relevance
“…However, the enhanced TB suspected symptoms in our study could help diagnose more active TB cases sooner, which was similar to that found in comparable studies [ 22 ]. Furthermore, compared with other studies in active screening for TB, our average screening costs for one active TB case was less than the same study in Russian Federation, despite the same level of TB incidence in both countries, but more than the studies in the higher TB-incidence countries [ 3 , 21 , 23 , 24 ]. In addition, if the active case-finding might be performed in targeted high-risk groups, the costs of performance could decrease undoubtedly.…”
Section: Discussioncontrasting
confidence: 50%
“…However, the enhanced TB suspected symptoms in our study could help diagnose more active TB cases sooner, which was similar to that found in comparable studies [ 22 ]. Furthermore, compared with other studies in active screening for TB, our average screening costs for one active TB case was less than the same study in Russian Federation, despite the same level of TB incidence in both countries, but more than the studies in the higher TB-incidence countries [ 3 , 21 , 23 , 24 ]. In addition, if the active case-finding might be performed in targeted high-risk groups, the costs of performance could decrease undoubtedly.…”
Section: Discussioncontrasting
confidence: 50%
“…This difference could be explained by the fact that only individuals with symptoms and abnormal CXR exam were eligible for sputum evaluation in the UTPS hence overestimation of the sensitivity at the cost of specificity. However, the use of the CXR increases the overall sensitivity hence an increased number of individuals being subjected to the confirmatory tests resulting into increased TB yield [ 21 , 22 ]. This is especially important in the era of the new advanced TB diagnostic tools such as the GeneXpert with high sensitivity and specificity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included stratified analyses among multiple high-risk populations and thus contributed results to multiple categories (i.e., clinical and/or structural risk factors). Seventeen studies included persons with clinical risk factors; [ 32 , 34 , 38 ] fourteen among PLHIV, the majority of which (12/14) were conducted in Sub-Saharan Africa (SSA) [ 29 32 , 37 , 39 42 , 44 , 45 , 49 , 52 , 53 ]. Thirteen studies included persons with structural risk factors (i.e., migrants, persons experiencing homelessness, or miners) and were from a range of countries such as Belgium, Cambodia, China, Russia, South Africa, and Zimbabwe [ 11 , 32 , 33 , 35 , 36 , 38 , 43 , 46 48 , 51 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies provided cost-effectiveness data for individuals with the following clinical risk factors: diabetes mellitus, chronic respiratory disease and fibrotic lesions (Table 3 ) [ 32 , 34 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation